Pengembangan Model Senam Aki (Aerobik Takikino) Di SD 11 Kota Barat - Dama, Mohamad Alimun; Said, Hariadi; Tumaloto, Ella H (Universitas Negeri Gorontalo, 2025)
This study aims to develop AKI (Aerobic Takikino) gymnastics at SD Negeri 11 Kota Barat. In aerobic gymnastics learning for students of Sd Negeri 11 Kota Barat which can be used to support learning so that students can more easily convey the material that has been taught, AKI (Aerobic Takikino) gymnastics also provides insight to students that Aerobic gymnastics can be used at every level of elementary school. This study is a type of RD (Research and Development) research. This research was developed using the Five Steps of the ADDIE development model, namely: 1). Analysis, 2). Design, 3). Development 4). Implementation, 5). Evaluation. The data collection technique in this study used insight, observation and questionnaires. This study produced AKI gymnastics (Aerobic Takikino). in aerobic gymnastics learning at SD Negeri 11 Kota in the form of learning media in the form of video books containing music, writing and pictures. Based on the validation that has been carried out by researchers on 3 experts, namely: gymnastics experts, learning experts and multi-media experts, it produced a value of 4 with a very appropriate category, the validation results showed that the AKI gymnastics development product (aerobic takikino) was suitable for use in gymnastics learning at SD Negeri 11 Kota Barat.